2018
DOI: 10.1007/s00586-018-5652-7
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage polarization contributes to local inflammation and structural change in the multifidus muscle after intervertebral disc injury

Abstract: These data support the proposal that macrophages and TNF (pro-inflammatory cytokine) play an active role in the subacute/early chronic phase of remodeling in muscle, adipose and connective tissues of the multifidus during IVD degeneration. This presents a novel target for treatment. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 63 publications
(137 reference statements)
1
66
0
Order By: Relevance
“…Although MSC treatment prevents fatty infiltration and fibrosis of the multifidus muscle after the development of an IVD lesion, it cannot prevent a muscle inflammatory response and muscle fiber transformation. These findings highlight the potential role of MSC therapy after IVD injury, but indicate other interventions may also be necessary to optimize recovery of spinal muscles such as the multifidis …”
Section: Discussionmentioning
confidence: 86%
“…Although MSC treatment prevents fatty infiltration and fibrosis of the multifidus muscle after the development of an IVD lesion, it cannot prevent a muscle inflammatory response and muscle fiber transformation. These findings highlight the potential role of MSC therapy after IVD injury, but indicate other interventions may also be necessary to optimize recovery of spinal muscles such as the multifidis …”
Section: Discussionmentioning
confidence: 86%
“…A recent study by James et al would point to a biochemical link. The authors showed, in an ovine IVD injury model, an increased proportion of pro-inflammatory M1 macrophages in paraspinal adipose tissue after disc injury, suggesting a local biochemical factors could mediate pain and inflammation in patients [55].…”
Section: Discussionmentioning
confidence: 97%
“…Polarization is directed by the local microenvironment and cytokine signaling. In an animal model of intervertebral disk lesions, immunofluorescence labeling of M1 and M2 macrophages indicated an increase in the proportion of M1 cells as well as an increase in TNF‐α expression, suggesting that M1 polarization plays a critical role in early stages of remodeling . In the case of knee OA, a study analyzing M1 macrophages and M2 macrophages in synovial fluid in normal versus OA knees found a higher ratio of M1/M2 in OA versus normal knees and the ratio was significantly correlated to the Kellgren‐Lawrence grade .…”
Section: Wound Healing—the Role Of the Macrophagementioning
confidence: 99%